2020
DOI: 10.1155/2020/3128053
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA-SNHG14 Promotes Atherosclerosis by Regulating RORα Expression through Sponge miR-19a-3p

Abstract: Coronary heart disease (CHD) is the most common cardiovascular disease with high prevalence, disability, and mortality. The balance between proliferation and apoptosis of vascular smooth muscle cells (VSMCs) plays a key role in the initiation of atherosclerosis. In this study, we found a significant decrease in the expression of lncRNA-SNHG14 in atherosclerotic plaque tissues of ApoE-/- mice. Overexpression of lncRNA-SNHG14 can inhibit VSMC proliferation while promoting apoptosis. There is a potential reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…27 Notably, miR-19a-3p is upregulated in atherosclerosis. 12 In addition, it has been reported that miR-19a-3p has a dual role in ischemic diseases. It can improve myocardial ischemia by regulating angiogenesis and myocardial fibrosis, 28 but also can promote ischemic stroke by interfering with glucose metabolism and promoting neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Notably, miR-19a-3p is upregulated in atherosclerosis. 12 In addition, it has been reported that miR-19a-3p has a dual role in ischemic diseases. It can improve myocardial ischemia by regulating angiogenesis and myocardial fibrosis, 28 but also can promote ischemic stroke by interfering with glucose metabolism and promoting neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 11 miR-19a-3p has been reported to be involved in atherosclerosis, and atherosclerosis is considered to be a common cause of CAS. 12 More importantly, in transient ischemic attack (TIA), a complication of CAS, glycine improves TIA by regulating miR-19a-3p to inhibit glucose metabolism, inflammation, and apoptosis. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism studies of LncRNAs showed that lncRNAs could regulate genes expression as miRNA sponges [ 21 , 22 ]. Therefore, the potential target miRNAs of SNHG10 were predicted by bioinformatics analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al con rmed that SNHG12 targets miR-199a-5p to regulate HIF-1α, thereby stimulating its proliferation and migration, and promoting the occurrence and development of AS[46]. Zhu, et al found that lncRNA SNHG14 can regulate miR-19a-3p/RORα axis through ceRNA mechanisms to inhibit the proliferation and promote apoptosis of VSMCs in AS, thus contributing to the development of AS[47].The peroxisome proliferator-activated receptors (PPARs) are ligand-activated nuclear TFs. PPARs are members of type II nuclear receptor superfamily and have multiple functions, such as inhibiting cell cycle progression from G1 to the S phase.…”
mentioning
confidence: 99%